Organização dos espaços na educação infantil brasileira: um levantamento de pesquisas acadêmicas (2009-2023) - Silva, Karen Simões (Universidade Federal de São Carlos, 2024)
The organization of spaces, from their architectural design to their use as part of the educational curriculum, occupies a central place in the daily life of early childhood education institutions. Given this, this work had the general objective of investigating, recording and understanding the contributions of Brazilian academic productions regarding the organization of internal and external spaces, spaces that children aged 0 to 5 attend in early childhood education institutions. For this research, methodological instruments of bibliographic research and document analysis were used with a qualitative approach, of the state of knowledge type. The time frame defined for the selection of academic productions was between the years 2009 and 2023. As a theoretical reference, the research was based on the historical context of early childhood education and the consolidation of its public policies, contributions from educational approaches and current studies on the subject. . This study allowed the mapping and presentation of academic productions selected through the chosen descriptors, present in the CAPES repository. From the reflections carried out by this work, several questions were revealed, some of which follow: the conception of space, attributed by these studies in relation to its physical characterization conferred by the objects that constitute it, the term environment understood as the junction of spaces physical with the relationships and interactions that occur within it and the term place understood as space/environment to which value was attributed by the subject; These spaces that make up the Early Childhood Education Institution are considered pedagogical resources and, depending on their organizations, provided by education professionals and architects, they can limit or favor the development and curiosity of babies and children; the space is not neutral and is a curricular element; uncoupling is urgent, due to the need for children and babies to have daily contact with the elements of nature in external spaces and the architecture of schools, which need to be designed together with education professionals and children and babies. In the end, it is concluded that all objectives were achieved.
Organization of spaces in Brazilian early childhood education: a bibliographic survey of academic research (2009-2023)
Keywords: Organização do Espaço; Educação Infantil; Educação; Arquitetura; Espaços; Space Organization; Child Education; Education; Architecture; Spaces; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO